EVALUASI BAHAYA DAN PENGENDALIAN RISIKO KECELAKAAN KERJA PADA PROYEK PENINGKATAN JALAN JENEBORA I DAN JENEBORA II KALIMANTAN TIMUR - Hikmah Maya Sari; abdullah (MECHA JURNAL TEKNIK MESIN, 2022)
The problem that still often occurs in the construction world is the low application of Occupational Safety and Health (K3) in construction projects. In this study, it will be evaluated how the implementation of the Occupational Health and Safety Management System (SMK3) in the Jenebora I and Jenebora II Road Improvement Project (Jenebora-Gersik), North Penajam Paser Regency, East Kalimantan. The purpose of this research is to find out how much understanding of workers and employees about the importance of OSH, to know how much understanding of workers and employees to the availability of guidelines, K3 guidelines, the purpose of implementing an OSH program, the presence of K3 experts and the importance of OHS experts, and to find out how to comply workers and employees on the implementation and implementation of the K3 program on the Jenebora I and Jenebora II (Jenebora-Gersik) Road Improvement Project work. This type of research is quantitative research. The research data were obtained from the results of filling out questionnaires and interviews. The number of samples in this study were 70 people. Data analysis used multiple linear analysis using the help of the Statistical Package for the Social Science (SPSS) version 26. The results showed that the understanding of workers and employees towards the provisions on OHS was on average above 70%, understanding of the availability of guidelines, OHS guidelines, the purpose of implementing them the K3 program, the presence of K3 experts and the importance of K3 experts by workers and employees on average above 70%, adherence to the implementation and implementation of the K3 program is an average of 80%, even the application of K3 rules that have met the established standards and worker obedience the obligation to use good and correct PPE to comply with standard K3 guidelines above 90%. Keywords: hazard evaluation, work accident risk control, multiple linear analysis